Pseudomonas aeruginosa Quorum Sensing Molecule N-(3-Oxododecanoyl)-l-Homoserine-Lactone Induces HLA-G Expression in Human Immune Cells - Bortolotti, Daria (Infect Immun, 2015)
HLA-G is a nonclassical class I human leukocyte antigen (HLA) involved in mechanisms of immune tolerance. The objective of this study was to determine whether N-(3-oxododecanoyl)-l-homoserine lactone (3O-C(12)-HSL), a quorum sensing molecule produced by Pseudomonas aeruginosa, could modify HLA-G expression to control the host immune response. We evaluated the ability of 3O-C(12)-HSL to induce HLA-G expression in primary immune cells, monocytes (U937 and THP1), and T-cell lines (Jurkat) in vitro and analyzed the cellular pathway responsible for HLA-G expression. We studied the HLA-G promoter with a luciferase assay and interleukin-10 (IL-10) and p38/CREB signaling with enzyme-linked immunosorbent assay and immunofluorescence, respectively. We observed that 3O-C(12)-HSL is able to induce HLA-G expression in human monocytes and T cells. We showed that the induction of HLA-G by 3O-C(12)-HSL is p38/CREB and IL-10 dependent. 3O-C(12)-HSL treatment is able to arrest only the U937 cell cycle, possibly due to the peculiar expression of the ILT2 receptor in the U937 cell line. Our observations suggest HLA-G as a mechanism to create a protected niche for the bacterial reservoir, similar to the role of HLA-G molecules during viral infections.